The efficacy and safety of current intravenous iron preparations for the management of iron-deficiency anaemia: a review - Qunibi, Wajeh Y (Arzneimittelforschung, 2010)
Iron-deficiency anaemia (IDA) is a major health problem worldwide, but responds well to iron supplementation. New approaches are leading to more effective management of this condition.Iron deficiency (ID) is usually suspected in at-risk patients with declining haemoglobin (Hb) levels and then confirmed by measuring serum ferritin levels and transferrin saturation. However, regular monitoring of these iron indicators and other laboratory parameters in susceptible individuals may lead to early recognition of falling iron stores and facilitate pre-emptive therapeutic intervention before anaemia develops.Patients with ID are commonly prescribed oral iron preparations because of convenience and low cost. However, the efficacy of these agents is limited by their reduced absorption rate and gastrointestinal side-effects. Alternatively, treatment of IDA in patients requiring erythropoiesis-stimulating agents (ESAs) is more predictably achieved by use of intravenous (i.v.) iron. Unfortunately, the development of serious adverse events (SAEs) from high molecular-weight iron dextran has led to reluctance to use i. v. iron in the treatment of IDA. Similarly, but to a much lesser extent, low molecular-weight iron dextran is associated with a number of SAEs, including allergic or anaphylactic reactions. The introduction of second-generation i.v. iron formulations, including iron sucrose and ferric gluconate, was clearly an improvement over i. v. iron dextran. These formulations proved to be effective in the management of IDA and are not associated with the serious allergic reactions encountered with i. v. iron dextran. For these reasons, use of these preparations became more widespread in the treatment of IDA across a wide range of clinical conditions. An important advantage of i. v. iron over oral iron is that it may bypass hepcidin actions by directly loading transferrin and making iron available to macrophages.Despite a reduction in the short-term risks, there is still concern about the potential for long-term toxicity of i. v. iron use (e. g. atherosclerosis development, infection and increased mortality). The association of atherosclerosis with iron overload remains unclear. Alternatively, the relative risk for mortality or hospitalization from infection in patients undergoing haemodialysis (HD) who received i. v. iron was shown not to be higher than that observed in the overall HD population. Indeed, doses of i. v. iron up to 400 mg/month were associated with improved patient survival.Second-generation i.v. iron formulations are more frequently used for treating IDA than i. v. iron-dextran in patients with various chronic conditions including those with chronic kidney disease. In the latter, IDA should be corrected before initiation of ESA therapy, as iron deficiency can lead to hyporesponsiveness to ESA. However, a major limitation of the second-generation i. v. iron agents is that they cannot be administered in large doses and the typical 1000 mg therapy requires several clinic visits. Thus, there is a need for an i. v. iron agent that can be safely administered in a single dose of 1000 mg of iron and therefore requires less frequent clinic visits. This limitation has now been overcome with the introduction of newer i. v. iron preparations.Ferric carboxymaltose offers effective and rapid correction of IDA by overcoming the limitations observed with previous i. v. iron preparations. This agent has been shown to be effective and well tolerated in a number of randomized controlled trials in a variety of chronic conditions.
Keywords: Anaemia; Ferric carboxymaltose, efficacy, safety; Intravenous iron; Iron deficiency